Cognitive Approaches to Grammar Teaching: An Article Review - Nur Ulyasari (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The cognitive approaches to grammar teaching, which is predicated on the notion that grammar is entwined with all other cognitive processes and structures, is clarified by means of an extensive literature survey conducted in this article. Reviewing the scholarly literature on the cognitive approaches and its connection to grammar was the study's main goal. Ten publications were classified as a result of the search being done in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards. The study's findings demonstrated that encouraging students to learn grammar via cognitive approaches make them more conscious of grammatical elements. Additionally, a number of factors, such as their opinions, attention, practice, and awareness, must be taken into account. A number of recurrent themes were also found in the literature review, including the importance of grammar to students and the efficacy of grammar education. Ultimately, it was discovered that while the cognitive approach presented certain difficulties in the context of teaching languages, it also demonstrated that pupils could readily identify the rules and conventions of grammar.